Globalization, growth, inequality and poverty in Africa: A macroeconomic perspective - Jeffery I. Round (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
The last two decades has witnessed an increase in globalizing influences affecting most countries, Africa included. These influences have arisen partly as a result of domestic and international policies, such as trade policies, and partly as a result of general globalizing impulses, such as technological developments and enhanced communications. The single overarching objective of this paper is to outline the macro evidence on the extent to which globalization is taking place and poverty is reducing in Africa, and to consider this to both characteristics of the region (i.e., within the region) and relative to other global regions. It draws on some of the most recent evidence about the globalizing processes in various forms so as to try to determine the speed and extent of globalization in Africa. This helps to put into proper perspective the impact of globalization on poverty and inequality. It is essentially a partial and descriptive approach, at best indicative of associations, and stops short of attempting to identify, empirically, channels of influence and causal relationships. – globalization ; inequality ; poverty ; Sub-Saharan Africa
Keywords: O11; O55; I30; 330; Globalisierung; Armut; Einkommensverteilung; Afrika südlich der Sahara